Propuesta para la creación del periódico digital llanosietedias en la ciudad de Villavicencio – Colombia (2022)
LLANOSIETEDIAS is a traditional media in the department of Meta, with a history of 29 years through which it has transmitted to its customers truthfulness, trust and seriousness in the information it presents. Its different areas of research, among which agriculture, health, science, technology and sports.